Analisa Kandungan Bahan Kimia Krom Dan Timbal Pada Limbah Cair Hasil Percobaan Praktikum Mahasiwa Pada Perguruan Tinggi Politeknik Akamigas Palembang - Achmad Faisal Faputri; Sri Ardhiany; Susanto Artan (Politeknik Akamigas Palembang, 2017)
The use of chemicals in Higher Education Akamigas Polytechnic is needed to conduct practical experiments, this is because all courses in polytechnic akamigas Palembang associated with chemicals that will be used so that will generate waste. To decrease the concentration of waste from the lab result so as not to pollute the environment which will result in various types of danger that can occur such as poisoning, irritation. Then to overcome it there is one such way by using the Adsorption process is one type of separation that serves to reduce levels of Chromium and Lead. Analysis of Chromium and Lead waste content to meet environmental quality standards and reduction of waste content using adsorption process with adsorbent is in the form of activated charcoal. From the result of waste analysis from the laboratory using spectrophotometric UV-Vis, Chromium and Lead waste content was found to be 121,08 ppm and 31,67 ppm above the specified environmental quality standard. Wastewater is lowered below the environmental quality standard with Chromium 0.153 ppm and lead of 0 ppm using 500 grams of active charcoal to 8 liters of waste water.